Cellular prion protein is present in dopaminergic neurons and modulates the dopaminergic system. (26th April 2014) - Rial, Daniel; Pamplona, Fabrício A.; Moreira, Eduardo L. G.; Moreira, Karin M.; Hipolide, Débora; Rodrigues, Diana I.; Dombrowski, Patrícia A.; Da Cunha, Claudio; Agostinho, Paula; Takahashi, Reinaldo N.; Walz, Roger; Cunha, Rodrigo A.; et al.
Abstract Cellular prion protein (PrPC) is widely expressed in the brain. Although the precise role of PrPC remains uncertain, it has been proposed to be a pivotal modulator of neuroplasticity events by regulating the glutamatergic and serotonergic systems. Here we report the existence of neurochemical and functional interactions between PrPC and the dopaminergic system. PrPC was found to co‐localize with dopaminergic neurons and in dopaminergic synapses in the striatum. Furthermore, the genetic deletion of PrPC down‐regulated dopamine D1 receptors and DARPP‐32 density in the striatum and decreased dopamine levels in the prefrontal cortex of mice. This indicates that PrPC affects the homeostasis of the dopaminergic system by interfering differently in different brain areas with dopamine synthesis, content, receptor density and signaling pathways. This interaction between PrPC and the dopaminergic system prompts the hypotheses that the dopaminergic system may be implicated in some pathological features of prion‐related diseases and, conversely, that PrPC may play a role in dopamine‐associated brain disorders.